2007
DOI: 10.1007/s11434-007-0437-0
|View full text |Cite
|
Sign up to set email alerts
|

Cretaceous synfolding remagnetization components revealing tectonic rotation of the middle Yangtze fold belt

Abstract: To reveal the deformation process of the middle Yangtze fold belt, we conducted a paleomagnetic study on Middle Triassic limestones and Middle to Late Jurassic sandstones from Wanzhou, Chongqing.Stepwise thermal and alternating field demagnetization were used to isolate the multi-component remanent magnetizations. The Jurassic samples were overprinted by recent geomagnetic field, while three magnetization components were isolated from the Middle Triassic samples. A low temperature component (LTC) was isolated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…The HTC components isolated from Jurassic samples in the Yunyang area are synfolding remagnetization components and reveal a clockwise rotation of 8 • since the late stage of folding. Triassic paleomagnetic data from this area suggested that this part of the fold belt had experienced a clockwise rotation of 13 • since the early stage of folding [20] . There is a 30 • difference in fold axis trend between the Wanzhou-Yunyang segments of the fold belt, whereas the rotation in this area is just 10 • .…”
Section: Origin Of the Curvature Between The Upper And Middle Yangtzementioning
confidence: 91%
See 2 more Smart Citations
“…The HTC components isolated from Jurassic samples in the Yunyang area are synfolding remagnetization components and reveal a clockwise rotation of 8 • since the late stage of folding. Triassic paleomagnetic data from this area suggested that this part of the fold belt had experienced a clockwise rotation of 13 • since the early stage of folding [20] . There is a 30 • difference in fold axis trend between the Wanzhou-Yunyang segments of the fold belt, whereas the rotation in this area is just 10 • .…”
Section: Origin Of the Curvature Between The Upper And Middle Yangtzementioning
confidence: 91%
“…Middle Triassic paleomagnetic results from the Yunyang area suggest that this part of the fold belt had experienced a clockwise rotation of 13 • ±4 • since the early stage of folding, thus supporting that at least part of clockwise rotations is due to oroclinal bending [20] . The HTC directions isolated from Jurassic samples of Yunyang area in our study are best clustered at 33.8% untilting, the mean direction is D=19.1 • , I=48.9 • (α 95 =6.3 • ), (the inclination is consistent with the reference one), corresponding to a paleopole at 73.5 • N, 198.2 • E (dp=5.5 • , dm=8.3 • ).…”
Section: Oroclinal Bending In Middle Yangtze Fold Beltmentioning
confidence: 92%
See 1 more Smart Citation
“…(a) Palaeomagnetic data of the Greater South China Block (the numbers in the black circles represent the literature sources: 1—Zhang & Yang, ; 2—Kirschvink et al, ; 3—Tan, Kodama, Gilder, Courtillot, & Cogne, ; 4—Han, Xu, Zhou, & Tan, ; 5—Zhang, Tan, & Han, ) and (b) the recovery of the Greater South China Block (Guo et al, )…”
Section: Dabie–sulu Oroclinementioning
confidence: 99%
“…While we are aiming to obtain a detailed paleomagnetic record from the relatively more expanded Late Cambrian succession from the Wa'ergang section to test and examine the Late Cambrian TPW in this study, we are fully aware of the extensive Mesozoic remagnetization that has been previously reported in South China (e.g., Dobson & Heller, ; Gao et al, ; Huang & Opdyke, ; Jing et al, ; Kent et al, ; Liu et al, ; Wang & Van der Voo, ; Zhang et al, ; Zhang et al, ). Although various remagnetization mechanisms have also been proposed (e.g., Gao et al, ; Huang & Opdyke, ; Jing et al, ; C. Liu, Ge, et al, ; Liu et al, ; Zhang et al, ), most previous studies focused on local processes leading to remagnetization.…”
Section: Introductionmentioning
confidence: 99%